2020
DOI: 10.3389/fbioe.2020.00857
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Processes Triggered by PEF for Astaxanthin Extraction From Xanthophyllomyces dendrorhous

Abstract: The aim of this study was to evaluate the potential of pulsed electric fields (PEF) to improve the extraction of the lipid-soluble astaxanthin from fresh biomass of a wild-type (CECT 11028) and mutant (ATCC 74219) Xanthophyllomyces dendrorhous strain using ethanol as solvent. Inactivation and propidium uptake studies revealed that inactivation is a good index for estimated the proportion of irreversible permeabilized cells when inactivation is higher than 70% in the two strains. Ethanol was ineffective for ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…This value is reached after 12 h of incubation for the biomass kept at either 25 • C or 37 • C. A longer incubation time (48 h) was necessary at 4 • C to yield a lipid bioaccessibility of 18.7 ± 1.6%. The reason why no further increase was reached could be that the incubation combined with PEF led to the coalescence of the lipid droplets in a large unique body, as previously shown, which was harder to access by digestive enzymes (Aguilar-Machado et al, 2020;Bensalem et al, 2018;Bodénès et al, 2016).…”
Section: Effect Of Incubation After Pef Treatment On Lipid Bioaccessi...mentioning
confidence: 92%
See 2 more Smart Citations
“…This value is reached after 12 h of incubation for the biomass kept at either 25 • C or 37 • C. A longer incubation time (48 h) was necessary at 4 • C to yield a lipid bioaccessibility of 18.7 ± 1.6%. The reason why no further increase was reached could be that the incubation combined with PEF led to the coalescence of the lipid droplets in a large unique body, as previously shown, which was harder to access by digestive enzymes (Aguilar-Machado et al, 2020;Bensalem et al, 2018;Bodénès et al, 2016).…”
Section: Effect Of Incubation After Pef Treatment On Lipid Bioaccessi...mentioning
confidence: 92%
“…Hydrophilic proteins were completely released after PEF in cell wall-free mutants, while wild-type cell wall-containing cells showed three times lower protein yields. Although several studies report that PEF does not have a direct impact on the cell wall (Bensalem et al, 2018;Papachristou et al, 2020;T Lam et al, 2017), an increase in the extractability of microalgae intracellular compounds (e.g., protein, lipid, pigments, carbohydrates) by organic solvents or buffer systems after PEF treatment has been described (Aguilar-Machado et al, 2020;Buchmann et al, 2019;Kempkes et al, 2015;Silve, Kian, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique requires low energy expenditure, easily scalable and nonthermal, and facilitates the purification of extracted compounds since it minimizes the release of cell debris. The pulse duration and electric field strength intensity are parameters that need to be optimized for each sample since they may change with a change in the electrical conductivity and texture of the sample (Saini and Keum, 2018;Aguilar-Machado et al (2020). It has been suggested that PEF also triggers some enzyme activity, which in turn accelerates the autolysis and the subsequent release of N-ASX.…”
Section: Nonconventional Extraction Methodsmentioning
confidence: 99%
“…17 This enhancing effect of after-PEF incubation has been suggested to be related to an autolysis process triggered by PEF, as already reported for yeasts. 18,19 In the case of microalgae, an analogous approach was performed for the carotenoid extraction from H. pluvialis by PEF treatment combined with a 6 h post-PEF aqueous incubation. 20 The authors observed an enormous release of the esterase enzyme in the supernatant of PEFtreated suspensions in the first hours after PEF, in comparison to the untreated ones.…”
Section: Introductionmentioning
confidence: 99%